I chempionatu Rossii po gimnastike - sto let - Arkayev, L. Ya. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to show the history of gymnastics in Russia from the first championships on gymnastics (1897) . Due to the efforts of Russian specialists the original domestic gymnastic school and the system of the elite gymnasts' training had been created. The author considers the new tendencies in Russian sports gymnastics'es development, he shows the main peculiarities of the new conception of elite gymnasts training in Russian National Team and analyses the difficulties and opportunities of the progress in mass gymnastics.